Are available models reliable for predicting the FRP contribution to the shear resistance of RC beams - Sas, Gabriel (2009)
In this paper the trustworthiness of the existing theory for predicting the FRP contribution to the shear resistance of reinforced concrete beams is discussed. The most well-known shear models for EBR (External Bonded Reinforcement) are presented, commented on and compared with an extensive experimental database. The database contains the results from more than 200 tests performed in different research institutions across the world. The results of the comparison are not very promising and the use of the additional principle in the actual shear design equations should be questioned. The large scatter between the predicted values of different models and experimental results is of real concern bearing in mind that some of the models are used in present design codes.